PELATIHAN PENGGUNAAN APLIKASI ME-HEALTH GO DALAM UPAYA PENGENDALIAN PERILAKU AGRESIF PADA SISWA REMAJA - Zidni Nuris Yuhbaba; M. Elyas Arif Budiman; Wahyi Sholehah Erdah Suswati (Jurnal Pengabdian Masyarakat, 2024)
Adolescence is a time of change in developmental and social domains which can be accompanied by behavioral problems such as aggressive behavior. Aggressiveness among adolescents can raise concerns about a teenager's mental health and is defined as a behavioral and emotional response that involves other people. Aggressive behavior can be a mental health problem for young adolescents and is defined as both behavioral and emotional in nature. Considering the importance of promoting mental health in adolescents, community service activities need to be carried out in teacher training using the me-health go application in an effort to aggressively control adolescent students at Jember High School. The training activity provided to teachers is in the form of an application called me-health go where the main focus of this application is prevention, early intervention, assessment and screening as well as additional mental health care through the application. The results of the community service activities carried out showed that of the 50 teachers who took part in training activities on using the me-health go application in an effort to control aggression among teenage students, 74% had good knowledge and 26% had sufficient knowledge. The results of the difference test using the Wilcoxon test showed that there was a difference in pretest and posttest knowledge with a p value of 0.000>0.05. Me health go is an application that helps teachers monitor adolescent mental health